ANALYSIS OF DETERMINATION OF THE GRAIN PURCHASE PRICES AT PT. PERTANI (PERSERO) UNIT PENGGILINGAN PADI (UPP) IN PINRANG REGENCY - Muh. Alwi; Nurlinda Habi; Jumriani Jumriani (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
Based on the Regulation of the Minister of Trade Number 24 of 2020 concerning Determination of Government Purchase Prices for Grain or Rice. Pricing is one that plays a big role in determining the success of a business, especially those engaged in buying and selling goods or company products. Determining this can be done in various ways, one of the most common is by adding a certain percentage of payment costs to all goods in the product. This study aims to analyze and find out the determination of the purchase price of grain applied to PT.Pertani (Persero) Paddy Milling Unit, Pinrang Regency. The data collection techniques used in this study were direct observation, interviews and documentation. The data analysis technique used in this research is descriptive qualitative analysis technique. The results in this study in setting the purchase price of grain is done manually. Even though there are rules that regulate it, it is difficult to make adjustments because of the conditions, location and conditions in the field. In purchasing grain, it must be according to predetermined standards, namely, having good quality, moisture content in the range of 22% -25%, the purchase price can vary because it is influenced by several factors, including weather, harvest amount, location, and price market.